Relationship Between Upper Respiratory Tract Infection And Acute Otitis Media In Children - Novita Prawitasari; Dahliah, Dahliah; Silva Sari C P; Hermiaty N; Syamsu Rijal (Jurnal EduHealth, 2025)
Upper respiratory tract infections (URTI) are common in children and often trigger complications like ear infection that can affect hearing and development . This study aims to analyze the relationship between URTI and ear infections in children through a qualitative literature review . The findings suggest that URTI, particularly viral infection like nasopharyngitis , can disrupt the function of the Eustachian tube, increasing the risk of ear infections . Other risk factors , such as the child's age , air pollution , and exposure to second hand smoke , also worsen this condition . Raising parental awareness about early detection and management of URTI, along with preventive measures like vaccination and maintaining a healthy environment , can help reduce ear infection incidence .